2018
DOI: 10.1038/s41598-017-17344-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of NaV1.2 and NaV1.6 in regulating neuronal excitability at febrile temperature and distinct contributions to febrile seizures

Abstract: Dysregulation of voltage-gated sodium channels (VGSCs) is associated with multiple clinical disorders, including febrile seizures (FS). The contribution of different sodium channel subtypes to environmentally triggered seizures is not well understood. Here we demonstrate that somatic and axonal sodium channels primarily mediated through NaV1.2 and NaV1.6 subtypes, respectively, behave differentially at FT, and might play distinct roles in FS generation. In contrast to sodium channels on the main axonal trunk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 72 publications
(77 reference statements)
4
75
0
1
Order By: Relevance
“…Fever and tachypnea were described in most of the medical records, which are nonspecific signs that may take place in several pathologies, being present before the occurrence of epileptic seizures in epileptic patients. The relation found in the present study between the occurrence of fever concomitant with leukocytosis, during and after epileptic seizures, has been discussed in a previous (12) . The authors described increased body temperature and leukocytosis as seizure-induced inflammatory responses in patients diagnosed with epileptic seizures.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Fever and tachypnea were described in most of the medical records, which are nonspecific signs that may take place in several pathologies, being present before the occurrence of epileptic seizures in epileptic patients. The relation found in the present study between the occurrence of fever concomitant with leukocytosis, during and after epileptic seizures, has been discussed in a previous (12) . The authors described increased body temperature and leukocytosis as seizure-induced inflammatory responses in patients diagnosed with epileptic seizures.…”
Section: Discussionsupporting
confidence: 64%
“…In children, the fact that fever episodes cause epileptic seizures may be explained by their higher CNS sensitivity, making this population more susceptible to febrile seizures. This is a benign and self-limiting diagnosis, affecting from 2% to 5% (12) . Thus, it can be inferred that the number of episodes of epileptic seizure can be reduced by treating the cause, in this case, the fever.…”
Section: Discussionmentioning
confidence: 99%
“…FGF14 also directly regulates the function of Nav1.2 and Nav1.6 channels at the axon initial segment. NaV1.2 is the main channel subtype implicated in the mediation of fever‐induced neuronal hyperexcitability 16 . This could explain why fever is a triggering factor in FGF14‐mutated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Without this increase in levels of WT VGSCs at the nodes of Ranvier, the Scn8a Δ9/Δ9 and Scn8a ∇3/∇3 homozygous mutants would demonstrate impaired nerve conduction. Though additional Western blotting and immunostaining would be necessary to confirm this hypothesis, previous studies have demonstrated that loss of Scn8a expression leads to the compensatory recruitment of other VGSC proteins, particularly Na v 1.2 (encoded by Scn2a ), to the mature nodes of Ranvier and axon initial segment . In further support of this hypothesis, Vega et al reported that Na v 1.2 protein levels are significantly upregulated in null Scn8a med‐Tg/med‐Tg mutants relative to WT littermates …”
Section: Discussionmentioning
confidence: 85%